2021
DOI: 10.1007/s00198-021-05881-y
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and undertreatment of osteoporosis in elderly patients undergoing total hip arthroplasty

Abstract: We detected a high prevalence of low bone mineral density assessed by DXA in 268 elderly patients with end-stage osteoarthritis scheduled for total hip arthroplasty (18% osteoporosis, 41% osteopenia). Therefore, and due to the identified concomitant undertreatment, routine DXA measurements should be considered in elderly patients prior to surgery. Introduction Bone quality represents a decisive factor for osseointegration, durability, and complications of an implanted prosthesis. Although the risk of osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…Interestingly, no differences in BMD were observed between elderly patients awaiting TKA and those scheduled for THA. While in our previous study [10], analyzing patients prior to THA, osteoporosis was diagnosed in 18% and osteopenia in 41%, in the present study osteoporosis was diagnosed in 17% and osteopenia in 46%. Also, no significant differences were measured at the individual DXA measurement sites between these two patient cohorts, indicating that the manifestation site of OA is independent of BMD or, in other words, that knee and hip OA equally affect BMD.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, no differences in BMD were observed between elderly patients awaiting TKA and those scheduled for THA. While in our previous study [10], analyzing patients prior to THA, osteoporosis was diagnosed in 18% and osteopenia in 41%, in the present study osteoporosis was diagnosed in 17% and osteopenia in 46%. Also, no significant differences were measured at the individual DXA measurement sites between these two patient cohorts, indicating that the manifestation site of OA is independent of BMD or, in other words, that knee and hip OA equally affect BMD.…”
Section: Discussioncontrasting
confidence: 54%
“…Owing to the considerable risk of osteoporosis in elderly patients with OA [8][9][10], the International Society for Clinical Densitometry (ISCD) recommends an assessment of bone mineral density (BMD) in women aged ≥ 65 years and men aged ≥ 70 years prior to orthopedic surgery, including TKA, to avoid adverse outcomes [11]. In TKA, poor bone status has been associated with intraoperative and periprosthetic fractures, migration of components, and aseptic loosening [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In patients aged ≥70 years qualified for THA, a high frequency of decreased BMD was found [16]. Our study confirms the reduced mineral content in this age group; at the same time, a bone density assessment should be considered before performing THA.…”
Section: Discussionsupporting
confidence: 81%
“…Our study confirms the reduced mineral content in this age group; at the same time, a bone density assessment should be considered before performing THA. On the other hand, studies indicate no correlation between the BMD of the femoral neck and cementless loosening after THA in 2-year follow-up in patients under 75 years of age without osteoporosis [16]. Patients with OA have been shown to have higher BMD compared to control, which is probably associated with increased sclerotization and remodeling within the joint [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, in concordance with the previous studies, 5 osteoporosis was identified from DXA and was defined as the BMD T-score of less than or equal to 22.5. 13 Based on our patient cohort, the rate of revision surgery in this study was 5.2% at a 3.7-year follow-up time (range: 2.1 to 5.2 years). Previous retrospective studies showed an increased risk of surgical failure in osteoporotic patients who underwent primary noncemented THA, with revision rates ranging between 2.2% and 8.9%.…”
Section: Figurementioning
confidence: 75%